Mitophagy–lysosomal pathway is involved in silver nanoparticle-induced apoptosis in A549 cells - Jiangyan Li; Xiaoru Chang; Mengting Shang; Shuyan Niu; Wenli Zhang; Bangyong Zhang; Wenyan Huang; Tianshu Wu; Ting Zhang; Meng Tang; Yuying Xue (Ecotoxicology and Environmental Safety, 2021)
With the increasing use of silver nanoparticles (AgNPs) in biological materials, the cytotoxicity caused by these particles has attracted much attention. However, the molecular mechanism underlying AgNP cytotoxicity remains unclear. In this study, we aimed to systematically investigate the toxicity induced by AgNP exposure to the lung adenocarcinoma A549 cell line at the subcellular and signaling pathway levels and elucidate the related molecular mechanism. The survival rate of cells exposed to AgNPs at 0, 20, 40, 80, and 160 μg/mL for 24 or 48 h decreased in a dose- and time-dependent manner. AgNPs induced autophagy and mitophagy, determined by the transmission electron microscopy investigation and upregulation of LC3 II/I, p62, PINK1, and Parkin expression levels. AgNP treatment induced lysosomal injury, including the decline of lysosomal membrane integrity and increase in cathepsin B level. The decreased in mitochondrial membrane potential, along with upregulation of cytochrome c, caspases 9 and 3, and BAX/BCL2, further suggested that mitochondrial injury were involved in AgNP-induced apoptosis. In addition, mitochondrial injury may further lead to excessive production of reactive oxygen species and oxidative/ antioxidant imbalance. The results suggested that AgNPs could regulate autophagy via mitochondrial and lysosome injury in A549 cells. The information of the molecular mechanism will provide an experimental basis for the safe application of nanomaterials.